Optimum Temperature and Time for Acid Hydrolysis in Reducing Sugar Manufacturing from Arabica Coffee Cascara with Response Surface Methodology (RSM) - Suryati, S; Meriatna, M; Masrullita, M; Safriwardy, Ferri; Ardiansyah, Ardiansyah (Universitas Malikussaleh, 2021)
This research aims to utilize the Arabica coffee cascara waste as a resource for reducing sugar production, including the investigation on the temperature and time required of the acid hydrolysis. The samples were initially pretreated (drying and milling), followed by delignification with the organosolv technique using alcohol. Then, the hydrolysis was carried out using sulfuric acid (1%) at a particular temperature (95, 100, and 105 °C) and time (2, 4, and 6 h) variations. Yield percentage, density, and reducing concentration were analyzed in each trial to generate a response surface methodology model. Based on the results, the hydrolysis can be optimized at 96.46 °C for 2.59 h, yielding 16.7696% reducing sugar.